Schizophrenia Patients with a History of Treating Shamans - Asyafaq, Abdul Hakam; Ragu Raman (Faculty of Medicine, Universitas Airlangga, 2026)
Introduction: Schizophrenia is a complex mental disorder. Almost 1% of the world’s population suffers from schizophrenia. Symptoms of schizophrenia usually begin under the age of 25 and can affect all social classes. The phenomenon that occurs in the community is that there are still families of schizophrenia sufferers who seek traditional treatment, such as a shaman, and then, if complaints do not improve, proceed to medical treatment. This report aims to show that prompt medical treatment can reduce psychotic symptoms rather than traditional treatment. Case: A 23-year-old female patient with paranoid schizophrenia was hospitalized for 3 days. The patient arrived at the hospital with complaints of not being able to sleep since 3 days ago, accompanied by seeing black shadows. Her family took her to a shaman before she sought treatment at the hospital. Discussion: The patient in this case suffered from paranoid schizophrenia. The patient had not been brought to the hospital since the age of 17, when the patient first experienced hallucinations. The patient responded well to the administration of second-generation antipsychotic drugs. The patient was discharged on day 3 of hospitalization and continued his antipsychotic medication at home. Conclusion: Effective treatment can reduce symptoms, reduce the likelihood of episodes of psychosis, shorten the duration of psychotic episodes, and allow the majority of people to live more productive lives. It is very important for the family to bring the patient to medical treatment rather than traditional treatment, such as seeing a shaman.